Water-controlling and oil-increasing resin sand and preparation method thereof
By forming a double-layer organic film on the surface of quartz sand and combining epoxy resin and phenolic resin, the problem of poor cementity of resin sand under low temperature conditions is solved, efficient water control and oil increase is achieved, extended sand prevention validity period, and improved stable oil field production ability.
Patent Information
- Application Number
- CN202411625713.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-11-14
AI Technical Summary
The existing technology cannot effectively cement and solidify under low temperature conditions, resulting in poor sand prevention effect of ordinary resin sand in oil wells and ineffective water control and oil increase, resulting in high sand yield rate of oil wells and short sand prevention period, which affects stable production in oil fields.
Quartz sand coated with organic films is used to form an inner and outer double-layer organic film on the surface of the quartz sand, and the combination of epoxy resin and phenolic resin, combined with hydroxylation modification and hydrophobic film technology, resin sand with high compressive strength is prepared. , enhance its hydrophobic properties and oil-phase permeability flux.
It effectively improves the compressive strength and hydrophobic properties of resin sand, significantly reduces the water content of the oil well, extends the sand prevention validity period, and improves the oil field's stable production capacity.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical sand control, and in particular relates to water-controlling and oil-increasing resin sand and a preparation method thereof. Background Art
[0002] The reserves of loose oil reservoirs account for about 70% of the world's hydrocarbon reserves. With the improvement of the degree of exploration and development, the sand production rate of such oil wells is getting higher and higher, which continuously increases the difficulty and cost of oil production. Oil well sand control has become one of the problems restricting the sustainable development of loose oil reservoirs. At the same time, long-term water injection or gas injection production in oil fields causes irreversible damage to the formation skeleton, causing loosening and cementation of oil well geology, and aggravating sand production in oil wells. After entering the water-containing development stage, the critical sand production pressure difference drops significantly, the effective period of sand control becomes shorter and shorter, and the comprehensive water content rises rapidly, making it more difficult to stabilize oil field production. Solving the problem of water control and oil production increase in medium and high water-containing oil wells has become a key research content in current oil field development.
[0003] According to the investigation, there are currently three technical means, including "blocking high-water-containing layers and fracturing low-water-containing layers" to solve the contradiction between interlayer production, "blocking high-water-containing high-permeability zones and fracturing low-permeability zones" to solve the contradiction within the layer, and injecting gel technology to change the oil-water permeability relationship. With the continuous deepening of water injection development in oil fields, some blocks have entered the "double high" development period of "highly dispersed remaining oil in the reservoir and high degree of water flooding in the main part", which has affected the effectiveness of sand control measures. The main manifestations are that after the implementation of sand control measures, the oil well fluid increase does not increase oil, the crude oil has a high water content, and the measures are short in effectiveness. Some oilfield reservoirs are shallowly buried and the formation temperature is low. Ordinary resin sand sand control particles cannot be cemented and solidified under low temperature conditions, and a sand control filtration barrier with a certain strength cannot be established, and the effect of sand control measures cannot be achieved.
[0004] A Chinese patent with announcement number CN103275686A discloses a water-controlling, low-temperature curing resin-coated sand control particle and a sand control method. The sand control particle includes a proppant, an inner resin film and an outer resin film coated on the outside of the proppant; wherein the inner resin film is a thermosetting phenolic resin film, and the outer resin film is a single-component polyurethane resin film. Two layers of resin films with different properties are coated on the surface of the proppant by adopting a thermal multi-layer coating method. The inner resin can be cemented and solidified into an insoluble and infusible three-dimensional structure under certain conditions, and has strong cementation and compressive strength. The outer resin is a single-component polyurethane resin that can form a film at room temperature, which can change the surface wettability of the sand control particle and the pore characteristics of the fracturing filling layer. The prepared sand control particles can effectively improve the effect of sand control measures in high water-content sand-producing blocks and reduce the water content of crude oil. A Chinese patent with announcement number CN115029124B discloses a fracturing water plugging resin sand and a preparation method thereof, which is composed of quartz sand, curing resin, plasticizing resin, dispersant and curing agent, wherein the curing resin and the plasticizing resin are wrapped on the surface of the core material, and are bonded to each other under heat or pressure to form a firm core cement body to prevent liquid phase penetration. Since the core cement body has quartz sand with high rigidity as the core material, it constitutes a rigid skeleton of the entire core cement body, so that the compressive strength of the core cement body is very high, the sealing surface is not easy to deform, and the sealing effect period is long.
[0005] However, the existing technology still has the problems of poor water control effect and great difficulty in stabilizing production. Therefore, how to effectively control water and increase oil production and improve the effect of sand control measures for oil and water wells is still a problem to be solved urgently in this field. Summary of the invention
[0006] In order to solve the problems existing in the prior art, the present invention provides a water-controlling and oil-increasing resin sand and a preparation method thereof, comprising skeleton sand, a curing agent and a dispersant, wherein the skeleton sand is quartz sand coated with an organic film, and an inner and outer double-layer organic film is formed on the surface of the quartz sand, so that the prepared resin sand has a good water-controlling and oil-increasing effect, thereby stabilizing the output of the oil field.
[0007] The technical solution adopted by the present invention to solve the above technical problems is: A water-controlling and oil-increasing resin sand comprises skeleton sand, a curing agent and a dispersant; the skeleton sand is quartz sand coated with an organic film, the organic film is divided into an inner layer and an outer layer, the inner layer is an n-octadecyl mercaptan organic film, and the outer layer is a composite organic film of thermosetting phenolic resin, epoxy resin and polydimethylsiloxane; the mass ratio of the skeleton sand, the curing agent and the dispersant is 10:0.2-0.285:0.01-0.015.
[0008] Coating an organic layer on the surface of quartz sand instead of quartz sand for extrusion filling and sand control can prevent a large amount of bottom water and edge water from entering the wellbore, thus playing a role in water control. Epoxy resin is a high molecular prepolymer or compound containing two or more epoxy groups. The active epoxy groups and side hydroxyl groups at the end of the epoxy resin structure give the resin reaction activity. The high polarity of hydroxyl groups and ether bonds causes strong intermolecular forces between epoxy resin molecules and adjacent interfaces. Before curing, epoxy resin has a thermoplastic linear structure and forms a three-dimensional network structure by reacting with a curing agent. The curing reaction of epoxy resin is completed by opening the epoxy ring. The active hydrogen first causes the electrophilic attachment of protons to the oxygen atom of the epoxy group to generate H3O + ions, this reaction is very rapid, in this H3O + Under the effect of ions, nucleophilic attack is carried out to open the epoxy ring, because the above-mentioned reaction does not need to eliminate small molecules and can make chain growth or crosslinking, so epoxy resin has lower curing shrinkage, and the ability of epoxy resin adhesion quartz sand is strong, acid and alkali resistance and excellent process performance, but epoxy resin has poor fluidity, and the crosslinking density after curing is high, and brittleness is large. Phenolic resin raw material price is cheap and processing technology is simple, and chemical stability is good, and acid resistance is strong. In the construction of rough surface, nanometer-level fine particles are very easy to flocculate into agglomerates, and it is necessary to first improve dispersibility to its surface super-hydrophobic modification, and in order to improve the adhesion of rough particles, the present invention adopts phenolic resin as binding agent, and phenolic resin can be consolidated under acidity or alkalinity. Therefore the present invention selects epoxy resin and phenolic resin to be composited, and the compressive strength of the resin sand obtained is higher.
[0009] Furthermore, the preparation method of the skeleton sand is: S1. Mix quartz sand and sodium hydroxide solution, heat in a water bath at 70-85°C and stir for 2-4h, then cool to room temperature, filter, wash and dry to obtain hydroxylated quartz sand; wherein the quartz sand is washed with deionized water for 3-5 times and then dried at 55-65°C for 10-15h; wherein the concentration of the sodium hydroxide solution is 0.2mol / L, and the amount of quartz sand in the sodium hydroxide solution is 0.02-0.06g / mL; The surface chemical activity of quartz sand is low, and it is not easy to react chemically with other substances. If it is directly mixed with resin, the bonding strength between it and the resin molecules is poor. Therefore, in the present invention, sodium hydroxide solution is used to hydroxylate the quartz sand to produce more highly chemically active hydroxyl groups on its surface, which is beneficial to the subsequent grafting reaction of the quartz sand.
[0010] S2, completely immersing the hydroxylated quartz sand obtained in step S1 in an ethanol solution of n-octadecanethiol, soaking it at room temperature for 2-4 hours, then taking it out and drying it at 80-90° C. for 2-4 hours, then soaking and drying it again, repeating 3-5 times, to obtain n-octadecanethiol-coated quartz sand; wherein the amount of the hydroxylated quartz sand in the ethanol solution of n-octadecanethiol is 0.2-0.6 g / mL; The n-octadecethiol molecule has a long-chain hydrophobic group and a thiol group structure, and the interaction force between the hydrophobic group and the material surface is relatively strong, and can interact with the surface active group to form an adsorption layer, forming a hydrophobic film on the material surface, reducing the surface energy, and enhancing the hydrophobic properties of the material. Therefore, n-octadecethiol is used in the present invention to modify the surface of quartz sand, and the obtained hydroxylated quartz sand is immersed in the ethanol solution of n-octadecethiol; there are a large number of hydroxyls on the surface of the hydroxylated quartz sand immersed in the ethanol solution, which can react with the sulfhydryl group in the thiol by dehydration condensation, and the bonding force between the quartz sand and the thiol is relatively strong through the linkage of chemical bonds, and it is not easy to fall off; in order to improve the film forming rate of n-octadecethiol on the surface of quartz sand, the hydroxylated quartz sand is repeatedly immersed in the ethanol solution of n-octadecethiol in the present invention to avoid not being thoroughly modified on the surface of quartz sand; the modification of quartz sand by n-octadecethiol can effectively reduce the surface energy of the material, so that it has the characteristics of super-hydrophobic-super-oleophilic; S3, adding thermosetting phenolic resin and epoxy resin to the acetone solution, stirring for 10-20 minutes, adding polydimethylsiloxane, stirring for 10-20 minutes, and then adding quartz sand coated with n-octadecyl mercaptan, soaking for 5-10 minutes, taking out, absorbing the surface solution, and drying at 50-60° C. for 20-40 minutes to obtain the skeleton sand; wherein the mass ratio of thermosetting phenolic resin, epoxy resin, polydimethylsiloxane, and quartz sand coated with n-octadecyl mercaptan is 10:8-12:0.02-0.04:25-35; the amount of thermosetting phenolic resin in the acetone solution is 0.2-0.4g / mL; The larger the surface energy, the easier it is for the solid surface to be wetted by the liquid, while the solid surface with low surface energy is not easily wetted by general liquids. Polydimethylsiloxane is a low surface energy chemical, so the present invention uses polydimethylsiloxane to modify the organic layer; when polydimethylsiloxane is added to an acetone solution containing a thermosetting phenolic resin and an epoxy resin, the presence of water in the solution can cause the polydimethylsiloxane to be hydrolyzed to generate a silanol bond structure, and the silanol bond reacts with the hydroxylated modified quartz sand at a certain temperature. At the same time, the silanol bond can polymerize with the -OR bond of the polydimethylsiloxane itself, and can also react with other silanol bonds to form a covalently bonded silane layer, and finally form polysiloxane particles with micro-nano structures after self-polymerization. These micro-nano particles can increase the surface roughness of the organic coating layer, further enhance the hydrophobic property, and thus increase the permeation flux of the oil phase.
[0011] Furthermore, the preparation process of the ethanol solution of n-octadecanethiol in step S2 is: dissolving n-octadecanethiol in anhydrous ethanol, stirring at room temperature for 30-40 minutes, to obtain the ethanol solution of n-octadecanethiol; wherein the amount of n-octadecanethiol in anhydrous ethanol is 0.002-0.004 g / mL.
[0012] Furthermore, the curing agent is a mixture of hexamethylenetetramine and polyamide curing agent in a mass ratio of 1:2-5.
[0013] Furthermore, the dispersant is calcium stearate.
[0014] The present invention also provides a method for preparing water-controlling and oil-increasing resin sand, the preparation process of which is: heating the skeleton sand to 75-95° C., adding a curing agent under stirring, stirring evenly for curing, and finally adding a dispersant and stirring until the material is dispersed, cooling, sieving, and packaging.
[0015] The present invention has the following beneficial effects: The present invention adopts epoxy resin and phenolic resin to coat the surface of quartz sand, which can effectively improve the compressive strength of the obtained resin sand. In the preparation process, the quartz sand is modified by hydroxylation so that more hydroxyl groups with high chemical activity are generated on the surface of the quartz sand, which can undergo dehydration condensation reaction with the thiol group in n-octadecethiol. Through the combination of chemical bonds, the quartz sand and the thiol have a strong binding force, and the n-octadecethiol can form a hydrophobic film on the surface of the material to enhance the hydrophobic property of the material. Furthermore, in the present invention, polydimethylsiloxane is used to modify the organic layer again. The polydimethylsiloxane can play a good hydrophobic role as a low surface energy chemical. The polydimethylsiloxane can be hydrolyzed when it meets water to generate a silanol bond structure. The silanol bond can polymerize with the -OR bond of the polydimethylsiloxane itself to form a covalently bonded silane layer, and finally self-polymerize to form polysiloxane particles with micro-nano structure, which can increase the surface roughness of the organic coating layer, further enhance the hydrophobic property, and thus improve the permeation flux of the oil phase. DETAILED DESCRIPTION
[0016] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0017] The quartz sand (analytical grade) and calcium stearate (chemically pure) used in the present invention were purchased from Tianjin Komeo Chemical Reagent Co., Ltd.; the epoxy resin (model: E-44) was purchased from Xi'an Resin Factory; the thermosetting phenolic resin (solid content 57%) was purchased from Jinan Shengquan Group, and the polyamide curing agent was polyamide 650, which was purchased from Jinan Shuangying Chemical Co., Ltd.; sodium hydroxide (analytical grade), acetone (analytical grade), hexamethylenetetramine (analytical grade), and anhydrous ethanol (analytical grade) were all purchased from Sinopharm Chemical Reagent Co., Ltd., n-octadecyl mercaptan (analytical grade) was purchased from Shanghai Titan Technology Co., Ltd., and polydimethylsiloxane (industrial grade) was purchased from Shin-Etsu Chemical of Japan. All reagents are commonly available on the market. Example 1
[0018] A water-controlling and oil-increasing resin sand comprises skeleton sand, a curing agent and a dispersant; the skeleton sand is quartz sand coated with an organic film, the organic film is divided into an inner layer and an outer layer, the inner layer is an n-octadecyl mercaptan organic film, and the outer layer is a composite organic film of thermosetting phenolic resin, epoxy resin and polydimethylsiloxane.
[0019] The preparation method of skeleton sand is: S1. Mix quartz sand and sodium hydroxide solution, heat in a water bath at 80°C and stir for 3 hours, then cool to room temperature, filter, wash and dry to obtain hydroxylated quartz sand; wherein the quartz sand is washed with deionized water 4 times and dried at 60°C for 12 hours; wherein the concentration of the sodium hydroxide solution is 0.2 mol / L, and the amount of quartz sand in the sodium hydroxide solution is 0.02 g / mL; S2, completely immersing the hydroxylated quartz sand obtained in step S1 in an ethanol solution of n-octadecyl mercaptan, soaking it at room temperature for 3 hours, then taking it out and drying it at 85° C. for 2 hours, then soaking it again and drying it, repeating it 4 times, to obtain n-octadecyl mercaptan-coated quartz sand; wherein the amount of the hydroxylated quartz sand in the ethanol solution of n-octadecyl mercaptan is 0.4 g / mL; S3. Add thermosetting phenolic resin and epoxy resin to acetone solution, stir for 15 minutes, then add polydimethylsiloxane and stir for 15 minutes, then add quartz sand coated with n-octadecyl mercaptan, soak for 8 minutes, take out, absorb the surface solution and dry at 55°C for 30 minutes to obtain skeleton sand; wherein the mass ratio of thermosetting phenolic resin, epoxy resin, polydimethylsiloxane and quartz sand coated with n-octadecyl mercaptan is 10:10:0.025:32; the amount of thermosetting phenolic resin in the acetone solution is 0.25 g / mL.
[0020] The preparation process of the ethanol solution of n-octadecyl mercaptan in step S2 is as follows: dissolving n-octadecyl mercaptan in anhydrous ethanol, stirring at room temperature for 35 minutes, and obtaining the ethanol solution of n-octadecyl mercaptan; wherein the amount of n-octadecyl mercaptan in anhydrous ethanol is 0.003 g / mL.
[0021] The curing agent is a mixture of hexamethylenetetramine and polyamide curing agent in a mass ratio of 1:3.
[0022] Wherein, the dispersant is calcium stearate.
[0023] A method for preparing water-controlling and oil-increasing resin sand comprises the following steps: heating 10 kg of skeleton sand to 85° C., adding 250 g of curing agent under stirring, stirring evenly and then curing, finally adding 12 g of dispersant and stirring until the material is dispersed, cooling, sieving and packaging. Example 2
[0024] Compared with Example 1, this embodiment has the following differences: In the preparation process of skeleton sand, step S1, after mixing quartz sand with sodium hydroxide solution, heating in a water bath at 70°C and stirring for 2 hours, wherein the mixture is washed with deionized water three times and then dried at 55°C for 10 hours; the amount of quartz sand in the sodium hydroxide solution is 0.02 g / mL; in step S2, the hydroxylated quartz sand obtained in step S1 is completely immersed in an ethanol solution of n-octadecyl mercaptan, soaked at room temperature for 2 hours, taken out and dried at 80°C for 2 hours, and then immersed and dried again, and repeated for 3 times, wherein the hydroxylated quartz sand is immersed in an ethanol solution of n-octadecyl mercaptan The amount used in the solution is 0.2 g / mL; in step S3, after adding thermosetting phenolic resin and epoxy resin to the acetone solution and stirring for 10 minutes, polydimethylsiloxane is added and stirred for 10 minutes, and then quartz sand coated with n-octadecyl mercaptan is added, soaked for 5 minutes, taken out, the surface solution is dried, and dried at 50° C. for 20 minutes, wherein the mass ratio of thermosetting phenolic resin, epoxy resin, polydimethylsiloxane, and quartz sand coated with n-octadecyl mercaptan is 10:8:0.02:25; the amount of thermosetting phenolic resin in the acetone solution is 0.2 g / mL.
[0025] In the preparation process of the ethanol solution of n-octadecyl mercaptan in step S2, n-octadecyl mercaptan is dissolved in anhydrous ethanol and stirred at room temperature for 30 minutes. The amount of n-octadecyl mercaptan in anhydrous ethanol is 0.002 g / mL.
[0026] The curing agent is a mixture of hexamethylenetetramine and polyamide curing agent in a mass ratio of 1:2.
[0027] A method for preparing water-controlling and oil-increasing resin sand comprises the following steps: heating 10 kg of skeleton sand to 75° C., adding 200 g of curing agent under stirring, stirring evenly and then curing, and finally adding 10 g of dispersant and stirring until the material is dispersed, cooling, sieving, and packaging.
[0028] The rest of the process is as in Example 1. Example 3
[0029] In the preparation process of skeleton sand, step S1, quartz sand and sodium hydroxide solution are mixed and heated in a water bath at 85°C and stirred for 4 hours, wherein the mixture is washed with deionized water 5 times and then dried at 65°C for 15 hours; the amount of quartz sand in the sodium hydroxide solution is 0.06 g / mL; in step S2, the hydroxylated quartz sand obtained in step S1 is completely immersed in an ethanol solution of n-octadecyl mercaptan, soaked at room temperature for 4 hours, taken out and dried at 90°C for 4 hours, and then immersed and dried again, and the process is repeated 5 times, wherein the hydroxylated quartz sand is immersed in an ethanol solution of n-octadecyl mercaptan The amount of the thermosetting phenolic resin in the acetone solution is 0.6 g / mL; in step S3, after adding thermosetting phenolic resin and epoxy resin to the acetone solution and stirring for 20 minutes, polydimethylsiloxane is added and stirred for 20 minutes, and then quartz sand coated with n-octadecyl mercaptan is added, soaked for 10 minutes, taken out, the surface solution is dried, and dried at 60° C. for 40 minutes, wherein the mass ratio of the thermosetting phenolic resin, epoxy resin, polydimethylsiloxane, and quartz sand coated with n-octadecyl mercaptan is 10:12:0.04:35; the amount of the thermosetting phenolic resin in the acetone solution is 0.4 g / mL.
[0030] In the preparation process of the ethanol solution of n-octadecyl mercaptan in step S2, n-octadecyl mercaptan is dissolved in anhydrous ethanol and stirred at room temperature for 40 minutes. The amount of n-octadecyl mercaptan in anhydrous ethanol is 0.004 g / mL.
[0031] The curing agent is a mixture of hexamethylenetetramine and polyamide curing agent in a mass ratio of 1:5.
[0032] A method for preparing water-controlling and oil-increasing resin sand comprises the following steps: heating 10 kg of skeleton sand to 95° C., adding 285 g of curing agent under stirring, stirring evenly and then curing, finally adding 15 g of dispersant and stirring until the material is dispersed, cooling, sieving and packaging.
[0033] The rest of the process is as in Example 1. Example 4
[0034] Compared with Example 1, this embodiment has the following differences: In the preparation process of skeleton sand, step S1, quartz sand and sodium hydroxide solution are mixed and heated in a water bath at 80°C and stirred for 2 hours, wherein the mixture is washed with deionized water three times and then dried at 60°C for 10 hours; the amount of quartz sand in the sodium hydroxide solution is 0.04 g / mL; in step S2, the hydroxylated quartz sand obtained in step S1 is completely immersed in an ethanol solution of n-octadecyl mercaptan, soaked at room temperature for 4 hours, taken out and dried at 85°C for 2 hours, and then immersed and dried again, and the process is repeated three times, wherein the hydroxylated quartz sand is immersed in an ethanol solution of n-octadecyl mercaptan The amount of the thermosetting phenolic resin in the acetone solution is 0.5 g / mL; in step S3, after adding thermosetting phenolic resin and epoxy resin to the acetone solution and stirring for 10 minutes, polydimethylsiloxane is added and stirred for 10 minutes, and then quartz sand coated with n-octadecyl mercaptan is added, soaked for 10 minutes, taken out, the surface solution is dried, and dried at 60° C. for 40 minutes, wherein the mass ratio of the thermosetting phenolic resin, epoxy resin, polydimethylsiloxane, and quartz sand coated with n-octadecyl mercaptan is 10:10:0.025:32; the amount of the thermosetting phenolic resin in the acetone solution is 0.3 g / mL.
[0035] In the preparation process of the ethanol solution of n-octadecanethiol in step S2, n-octadecanethiol is dissolved in anhydrous ethanol and stirred at room temperature for 40 minutes. The amount of n-octadecanethiol in anhydrous ethanol is 0.0025 g / mL.
[0036] The curing agent is a mixture of hexamethylenetetramine and polyamide curing agent in a mass ratio of 1:2.5.
[0037] A method for preparing water-controlling and oil-increasing resin sand comprises the following steps: heating 10 kg of skeleton sand to 95° C., adding 210 g of curing agent under stirring, stirring evenly and then curing, finally adding 11 g of dispersant and stirring until the material is dispersed, cooling, sieving and packaging.
[0038] The rest of the process is as in Example 1.
[0039] Comparative Example 1 Compared with Example 1, this comparative example does not add n-octadecyl mercaptan during the preparation of skeleton sand, specifically: The preparation process of skeleton sand is as follows: S1. Mix quartz sand and sodium hydroxide solution, heat in a water bath at 80°C and stir for 3 hours, then cool to room temperature, filter, wash and dry to obtain hydroxylated quartz sand; wherein the quartz sand is washed with deionized water 4 times and dried at 60°C for 12 hours; wherein the concentration of the sodium hydroxide solution is 0.2 mol / L, and the amount of quartz sand in the sodium hydroxide solution is 0.02 g / mL; S2. Add thermosetting phenolic resin and epoxy resin to acetone solution, stir for 15 minutes, then add polydimethylsiloxane and stir for 15 minutes, then add hydroxylated quartz sand, soak for 8 minutes, take out, absorb the surface solution and dry at 55°C for 30 minutes to obtain skeleton sand; wherein the mass ratio of thermosetting phenolic resin, epoxy resin, polydimethylsiloxane and hydroxylated quartz sand is 10:10:0.025:32; the amount of thermosetting phenolic resin in acetone solution is 0.25 g / mL.
[0040] The rest of the process is as in Example 1.
[0041] Comparative Example 2 Compared with Example 1, in the preparation process of skeleton sand, polydimethylsiloxane is not added in this comparative example, specifically: The preparation process of skeleton sand is as follows: S1. Mix quartz sand and sodium hydroxide solution, heat in a water bath at 80°C and stir for 3 hours, then cool to room temperature, filter, wash and dry to obtain hydroxylated quartz sand; wherein the quartz sand is washed with deionized water 4 times and dried at 60°C for 12 hours; wherein the concentration of the sodium hydroxide solution is 0.2 mol / L, and the amount of quartz sand in the sodium hydroxide solution is 0.02 g / mL; S2, completely immersing the hydroxylated quartz sand obtained in step S1 in an ethanol solution of n-octadecyl mercaptan, soaking it at room temperature for 2 hours, then taking it out and drying it at 85° C. for 2 hours, then soaking and drying it again, repeating it 4 times, to obtain n-octadecyl mercaptan-coated quartz sand; wherein the amount of the hydroxylated quartz sand in the ethanol solution of n-octadecyl mercaptan is 0.4 g / mL; S3. Add thermosetting phenolic resin and epoxy resin to acetone solution, stir for 15 minutes, then add quartz sand coated with n-octadecyl mercaptan, soak for 8 minutes, take out, absorb the surface solution and dry at 55°C for 30 minutes to obtain skeleton sand; wherein the mass ratio of thermosetting phenolic resin, epoxy resin and quartz sand coated with n-octadecyl mercaptan is 10:10:32; the amount of thermosetting phenolic resin in the acetone solution is 0.25 g / mL.
[0042] The rest of the process is as in Example 1.
[0043] Comparative Example 3 Compared with Example 1, in the preparation process of skeleton sand, the quartz sand is not subjected to hydroxylation modification, specifically: The preparation process of skeleton sand is as follows: S1. Completely immerse the quartz sand in the ethanol solution of n-octadecyl mercaptan, soak at room temperature for 2 hours, then take out and dry at 85° C. for 2 hours, then soak again and dry, repeat 4 times to obtain quartz sand coated with n-octadecyl mercaptan; wherein the amount of quartz sand in the ethanol solution of n-octadecyl mercaptan is 0.4 g / mL; S2. Add thermosetting phenolic resin and epoxy resin to acetone solution, stir for 15 minutes, then add polydimethylsiloxane and stir for 15 minutes, then add quartz sand coated with n-octadecyl mercaptan, soak for 8 minutes, take out, absorb the surface solution and dry at 55°C for 30 minutes to obtain skeleton sand; wherein the mass ratio of thermosetting phenolic resin, epoxy resin, polydimethylsiloxane and quartz sand coated with n-octadecyl mercaptan is 10:10:0.025:32; the amount of thermosetting phenolic resin in the acetone solution is 0.25 g / mL.
[0044] The rest of the process is as in Example 1.
[0045] Comparative Example 4 Compared with Example 1, the skeleton sand in this comparative example is quartz sand, and the quartz sand is not modified, specifically: The preparation process of skeleton sand is as follows: add thermosetting phenolic resin and epoxy resin to acetone solution, stir for 15 minutes, then add quartz sand, soak for 8 minutes, take out, absorb the surface solution and dry at 55°C for 30 minutes to obtain skeleton sand; the mass ratio of thermosetting phenolic resin, epoxy resin and quartz sand is 10:10:32; the amount of thermosetting phenolic resin in acetone solution is 0.25g / mL.
[0046] The rest of the process is as in Example 1.
[0047] Related tests: Preparation of core: Pour the prepared resin sand into a beaker, add an appropriate amount of hydrochloric acid with a mass concentration of 3%, and stir for 1 minute; remove the sand-proof particles and put them into a stainless steel cylinder with copper mesh at both ends, and tighten the stainless steel cylinder with a screw with a hole in the center; then immerse one end of the steel cylinder with a screw into the hydrochloric acid with a mass concentration of 3%, and use an ear suction bulb at the other end to suck the acid into the stainless steel cylinder, seal it, and put it in a water bath, and solidify it at above 25°C for 48 hours to make a core. Among them, those skilled in the art can adjust the amount of resin sand according to the size and shape of the required core.
[0048] The resin sand prepared in Example 1 was prepared into two cores with exactly the same shape, size and amount of resin sand by the above-mentioned method. The cores were placed in a core permeability tester, one of which was continuously soaked and rinsed with clean water, and the other was continuously soaked and rinsed with kerosene. On the 10th, 20th, 30th and 40th day of soaking and rinsing, the oil phase permeability and water phase permeability of the above two cores were measured; similarly, the resin sand prepared in Examples 2-4 and Comparative Examples 1-4 were prepared and tested in the above manner, and the test results are shown in Table 1. Among them, the determination and calculation methods of oil phase permeability and water phase permeability are conventional techniques in the field.
[0049] Table 1 Permeability test results
[0050] From the above results, it can be seen that the resin sand prepared in Examples 1-4 of the present invention has better water control and oil increase effects than Comparative Examples 1-4, especially Example 1 has the best effect, and its oil phase permeability still reaches 42 μm after continuous kerosene flow for 40 days. 2 The water permeability is less than 20μm when the water is continuously passed for 40 days. 2 .
[0051] The resin sand prepared in Examples 1-4 and Comparative Examples 1-4 was subjected to a medium immersion resistance test. The detection method was based on the method described in the literature "Zhang Fusheng, Zhang Huaibin, et al., "Development of Cheap Low-Temperature Sand Control Agents" [J]. Special Oil and Gas Reservoirs, 2007, 14 (1) 76-79". The detection results are shown in Table 2.
[0052] Table 2 Results of medium immersion resistance test
[0053] It can be seen from the test results in Table 2 that, compared with comparative examples 1-4, the resin sand prepared in embodiments 1-4 of the present invention has good compressive strength and acid and alkali resistance, especially embodiment 1 has the best performance.
[0054] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0055] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.
Claims
1. A water-controlling and oil-increasing resin sand, characterized in that: It includes skeleton sand, curing agent and dispersant; the skeleton sand is quartz sand coated with an organic film, the organic film is divided into an inner layer and an outer layer, the inner layer is an organic film of n-octadecyl mercaptan, and the outer layer is a composite organic film of thermosetting phenolic resin, epoxy resin and polydimethylsiloxane; the mass ratio of skeleton sand, curing agent and dispersant is 10:0.2-0.285:0.01-0.
015.
2. The water-controlling and oil-increasing resin sand according to claim 1, characterized in that: The preparation method of the skeleton sand is: S1. Mix quartz sand and sodium hydroxide solution, heat in a water bath at 70-85° C. and stir for 2-4 hours, then cool to room temperature, filter, wash and dry to obtain hydroxylated quartz sand; S2, completely immersing the hydroxylated quartz sand obtained in step S1 in an ethanol solution of n-octadecyl mercaptan, soaking it at room temperature for 2-4 hours, then taking it out and drying it at 80-90° C. for 2-4 hours, then soaking and drying it again, and repeating it 3-5 times to obtain n-octadecyl mercaptan-coated quartz sand; S3. Add thermosetting phenolic resin and epoxy resin to the acetone solution and stir for 10-20 minutes, then add polydimethylsiloxane and stir for 10-20 minutes, then add quartz sand coated with n-octadecyl mercaptan, soak for 5-10 minutes, take out, absorb the surface solution and dry to obtain the skeleton sand.
3. The water-controlling and oil-increasing resin sand according to claim 2, characterized in that: In step S1, the product is washed with deionized water for 3-5 times and then dried at 55-65° C. for 10-15 hours.
4. The water-controlling and oil-increasing resin sand according to claim 2, characterized in that: The preparation process of the ethanol solution of n-octadecanethiol in step S2 is as follows: dissolving n-octadecanethiol in anhydrous ethanol, stirring at room temperature for 30-40 minutes, to obtain the ethanol solution of n-octadecanethiol.
5. The water-controlling and oil-increasing resin sand according to claim 2, characterized in that: The drying condition in step S3 is drying at 50-60° C. for 20-40 min.
6. The water-controlling and oil-increasing resin sand according to claim 1, characterized in that: The curing agent is a mixture of hexamethylenetetramine and polyamide curing agent in a mass ratio of 1:2-5.
7. The water-controlling and oil-increasing resin sand according to claim 1, characterized in that: The dispersant is calcium stearate.
8. The method for preparing water-controlling and oil-increasing resin sand according to any one of claims 1 to 7, characterized in that: The preparation process is as follows: heat the skeleton sand to 75-95°C, add the curing agent while stirring, stir evenly to solidify, finally add the dispersant and stir until the material is dispersed, cool, sieve and package.
Citation Information
Patent Citations
Water-control low-temperature curing resin coated sand control particle and sand control method
CN103275686A
A fracturing and water-plugging resin sand and its preparation method
CN115029124B
Epoxy resin adhesive using modified multielement sulfur alcohol as solidifying agent and preparation method thereof
CN102086363A
High-temperature-resistant sand-control support agent and high-temperature-resistant sand-control curing system
CN103173195A
Low-temperature delayed-curing sand-control proppant, preparation method of proppant as well as low-temperature delayed-curing sand-control system
CN105112043A
